Crowdfunding, a new agricultural investment model driven by young entrepreneurs - Sall, Mamadou (Technical Centre for Agricultural and Rural Cooperation, 2019)
Faced with the lack of available finance for agricultural businesses from traditional banks, innovative entrepreneurs are turning to digital technology to access investment from the general public. Crowdfunding platforms have many advantages, but also entail some risks if there is to be trouble-free development of this alternative source of finance.